Zofia Hertz w świetle korespondencji z ojcem (1945–1958) - Łabno, Kamila (Archiwum Emigracji, 2016)
ZOFIA HERTZ IN THE LIGHT OF HER CORRESPONDENCE WITH HER FATHER (1945–1958) The article is a documentation and an interpretation of the correspondence between Zofia Hertz and her father Ludwik Neuding. The 111 letters written between 1945 and 1958 are a testament of great and “small” history, comprising biographical snippets of the co-founder of the Literary Institute. An introduction to an epistolographic presentation is the biography depicted in an abbreviated form: a difficult childhood and the separation from her motherland being a prelude to the first letter from her father which she received just after the war had ended. The presented material enables us to perceive Zofia not only as a woman creating a literary world in exile, but, most importantly, as a daughter, who despite having a complicated relationship with her father still supported him using all available means and ways. It is also—on the other hand—a testament of fatherly worries and “live coverage” from a country near, yet distant, which “liberated” Poland was for Zofia.